The Nickel Boys : a Novel - Whitehead, Colson 1969- (New York : Doubleday, 2019)
Follows the experiences of two African-American teenagers at an abusive reform school in Jim Crow-era Florida.
Includes bibliographical references.
Keywords: African American teenagers -- Fiction; Reformatories -- Fiction -- Florida; African Americans -- Fiction -- Segregation; Racism -- Fiction -- United States; United States -- Fiction -- Race relations; Florida -- Fiction; Historical fiction